Structural and Biological Studies on Transition Metal Complexes of 4-Aminoantipyrine Derivative - Soundaranayaki, V.; Kulandaiswamy, A. (Asian Journal of Chemistry, 2020)
Novel tetra dentate Cu(II), Ni(II), Co(II), VO(II) and Zn(II) Schiff base complexes have been synthesized from salicylidene-4-iminoantipyrine and tyrosine. The synthesized Schiff base complexes was characterized by powder X-ray diffraction studies (XRD), scanning electron microscopy (SEM), FT-IR, ESR, 1H NMR, 13C NMR, UV-vis, molar conductance and magnetic susceptibility measurements. The general formula of complexes was confirmed as [ML] type [M = Cu(II), Co(II), Zn(II), Ni(II) and VO(II); L = C27H24N4O4]. Magnetic susceptibility, IR and UV-vis, spectral data showed that all the complexes have square planar geometry except vanadyl complex which suggests square pyramidal geometry. Lower molar conductance values proved that all the chelates were non-electrolytic nature. The X-band ESR spectra of [CuL] and [VOL] complexes in DMSO solution suggest that the complexes were predominant covalent character. Powder XRD and SEM image pattern evidenced that all the compounds were crystalline in nature and their size ranges from 100-40 nm. Calf thymus DNA binding potential of [CuL] and [VOL] complexes shows that the binding occurs through intercalation mode with low binding constant. The analgesic, CNS, antiulcer and antimicrobial activities of the investigated compounds report reveals that the chelates were significant effect than free Schiff base.